The philosophy of pharmaceutical regulation—Paternalism or freedom of choice? - Mahlich, Jörg; Riou, Sybille; Verry, Matthieu (Frontiers in Medicine, 2023)
When assessing the value of new drugs regulatory authorities across the world frequently make different decisions even though their decisions are based on the same evidence package. In this perspective we argue that even in today's world regulatory and medical decision making is framed by conflicting philosophical schools of thought, namely the liberal tradition of the Anglo Saxon countries pioneered by the Scotsman Adam Smith and the continental European tradition of paternalism that roots back to the German philosopher Georg Friedrich Hegel. We outline the basics of these two philosophical theories and show that countries following the liberal tradition are more reluctant to reject new drugs due to weak evidence. Instead, they leave decisions to a greater extend to those who are affected, namely patients and their caregivers.